(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The evolution of Green Chemistry concepts and the field’s basic principles are discussed. There are examples of how these ideas are applied in many fields of chemistry. In preparative organic chemistry, the often employed alternative solvents (green solvents – water, PEG, per fluorinated solvents, supercritical liquids) are explained. Green chemistry’s current and future advances in education and organic chemical technologies are discussed.